2015
DOI: 10.1371/journal.pone.0135772
|View full text |Cite
|
Sign up to set email alerts
|

When Eating Right, Is Measured Wrong! A Validation and Critical Examination of the ORTO-15 Questionnaire in German

Abstract: The characteristic trait of individuals developing a pathological obsession and preoccupation with healthy foods and a restrictive and avoidant eating behavior is described as orthorexia nervosa (ON). For ON, neither universal diagnosis criteria nor valid tools for large-scale epidemiologic assessment are available in the literature. The aim of the current study is to analyze the psychometric properties of a translated German version of the ORTO-15 questionnaire. The German version of the ORTO-15, a eating beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
151
3
13

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(177 citation statements)
references
References 32 publications
10
151
3
13
Order By: Relevance
“…Our results indicated that vegetarian diet was directly associated with higher levels of all aspects of orthorexia nervosa (knowledge of healthy eating, problems associated with healthy eating and feelings positively about healthy eating) (H1 was confirmed). These findings are in line with prior studies in the literature that also find that higher rate of orthorexic behaviors was linked to a vegetarian diet [12,17,[40][41][42]. It can be supposed that a vegetarian diet might increase the risk of developing orthorexia nervosa [11].…”
Section: Discussionsupporting
confidence: 91%
“…Our results indicated that vegetarian diet was directly associated with higher levels of all aspects of orthorexia nervosa (knowledge of healthy eating, problems associated with healthy eating and feelings positively about healthy eating) (H1 was confirmed). These findings are in line with prior studies in the literature that also find that higher rate of orthorexic behaviors was linked to a vegetarian diet [12,17,[40][41][42]. It can be supposed that a vegetarian diet might increase the risk of developing orthorexia nervosa [11].…”
Section: Discussionsupporting
confidence: 91%
“…Another research previously described the increased rate of ON among ED patients after treatment (Segura Garcia et al 2015). Two explanations can be given to this result: a) this orthorexic score could be an iatrogenic-like side effect of CBT, but according to clinical interview was not confirmed, b) the result was a false positive: a recent research has highlighted the lack of statistical power of the ORTO-15 (Missbach et al 2015).…”
Section: Case Illustration: Presentationmentioning
confidence: 93%
“…On the other hand, Italy has a widely recognized culture about eating and nutrition and the Mediterranean diet has long been praised for its general health benefits and a strong attention paid to taste [58]; a similar situation is found in the Northeast (Basque Country) region of Spain.…”
Section: Comparison Among the Italian Polish And Spanish Samplesmentioning
confidence: 95%